A magnesium-based composite material with high hydrolysis hydrogen production conversion rate and preparation method thereof
By preparing Mg-Ca binary alloy and adding composite metal carbide and transition metal Ni to form Mg-Mg2Ca-composite metal carbide-Ni composite powder, the problem of low conversion rate of hydrogen production by hydrolysis of magnesium-based materials is solved, and high efficiency is achieved. The hydrolysis hydrogen production conversion rate and rapid hydrogen production rate.
Patent Information
- Application Number
- CN202410962366.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-18
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-07-18
AI Technical Summary
The magnesium-based material forms dense colloidal Mg(OH)2 by-products during hydrolysis, resulting in a low conversion rate of hydrogen production and a slow reaction rate.
By preparing Mg-Ca binary alloy and adding composite metal carbides TiC, ZrC and transition metal Ni during ball milling, Mg-Mg2Ca-composite metal carbide-Ni composite powder is formed, utilizing its ultra-high hardness and electron transfer effect , accelerating electron transfer and hydrogen diffusion during hydrolysis.
It significantly improves the hydrolysis hydrogen production conversion rate of magnesium-based composite materials, reaching more than 99.0%, and accelerates the hydrogen production rate, making it suitable for mobile hydrogen production applications.
Smart Images

Figure CN118877837B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a magnesium-based composite material with high hydrolysis hydrogen production conversion rate and a preparation method thereof, belonging to the technical field of hydrogen production materials and preparation processes thereof. Background Art
[0002] In recent years, various hydrogen-powered devices such as hydrogen-powered cars, ships, engineering vehicles, and portable power sources have developed rapidly. Hydrogen is generally considered to be an ideal renewable energy carrier due to its high energy density, zero pollution, and abundant reserves. In order to realize the commercial application of hydrogen energy, it is necessary to develop cheap and green hydrogen production technology, safe and reliable hydrogen storage technology, and reasonable and efficient hydrogen use technology. However, to date, cheap and pollution-free hydrogen production technology remains a challenge.
[0003] As a new type of hydrogen source, metal hydrogen production materials can react with water to generate hydrogen in situ under mild conditions, providing a new option for hydrogen supply. The hydrogen produced by hydrolysis can be used immediately without the need for storage or transportation. Magnesium, as a hydrogen production material, has the advantages of high electrochemical activity, high hydrogen production, low cost, and no pollution. Under standard conditions, the theoretical hydrogen production can reach 921mL g -1 However, the dense colloidal Mg(OH)2 byproduct is easily formed on the Mg surface during the hydrolysis process, which is a key obstacle to achieving rapid hydrolysis and high hydrogen production rate of magnesium-based materials, resulting in low conversion rate of hydrogen production by hydrolysis and slow reaction rate. Through reasonable structural design and catalytic modification, it is expected to accelerate the rate of hydrogen production by hydrolysis and improve the conversion rate of hydrogen production at the same time, which is of great significance for the industrial application of magnesium-based materials in the field of mobile hydrogen production. Summary of the invention
[0004] The purpose of the present invention is to provide a magnesium-based composite material with a high hydrolysis hydrogen production conversion rate, and the hydrogen production amount is close to 100% conversion rate, in order to address the key problems of low hydrolysis hydrogen production conversion rate, slow hydrogen production rate and low material utilization rate of magnesium-based materials.
[0005] At the same time, the present invention provides a method for preparing a magnesium-based composite material with a high hydrolysis hydrogen production conversion rate. The method is based on the spontaneous reaction of the Mg2Ca phase with water: Mg2Ca+6H2O→2Mg(OH)2+Ca(OH)2+3H2↑, with a high hydrogen production rate, and the eutectic structure of the Mg-Ca binary alloy is a typical lamellar structure, and the two phases are alternately distributed, which can effectively prevent the formation of dense Mg(OH)2 and Ca(OH)2. The ultra-high hardness of metal carbides TiC and ZrC and the electron transfer effect between them and metal Mg are utilized to effectively refine the alloy particle size and microstructure during the ball milling process, and at the same time, the transition metal Ni is efficiently distributed on the particle surface and subsurface, so that it forms a battery with the matrix Mg and Mg2Ca phases, accelerates electrochemical corrosion, and promotes electron transfer and hydrogen diffusion in the hydrolysis process through the bridge effect of TiC and ZrC, thereby improving the hydrolysis hydrogen production conversion rate of the matrix.
[0006] At the same time, the present invention provides a magnesium-based composite material with a high hydrolysis hydrogen production conversion rate for use in mobile hydrogen production.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0008] A method for preparing a magnesium-based composite material with a high hydrolysis hydrogen production conversion rate comprises the following steps:
[0009] Step 1, preparing Mg-Ca binary alloy;
[0010] Step 2, mechanically crushing the obtained Mg-Ca binary alloy to obtain Mg-Mg2Ca alloy particles;
[0011] Step 3, adding composite metal carbide and Ni powder to the Mg-Mg2Ca alloy particles and performing high-energy ball milling to obtain Mg-Mg2Ca-composite metal carbide-Ni composite powder;
[0012] Step 4: Place the Mg-Mg2Ca-composite metal carbide-Ni composite powder into a tablet pressing mold, and use a tablet pressing machine to press it into a block or sheet material to obtain a magnesium-based composite material with a high hydrolysis hydrogen production conversion rate.
[0013] Preferably, in the Mg-Ca binary alloy, the mass fraction of the Ca element ranges from 8% to 16%, and the balance is Mg.
[0014] Preferably, in the Mg-Mg2Ca-composite metal carbide-Ni composite powder, the composite metal carbide is TiC and ZrC in a mass ratio of 1:1; the mass fraction of the composite metal carbide is 3% to 5%, and the mass fraction of Ni is 4% to 8%.
[0015] Preferably, in step one, the preparation method of the Mg-Ca binary alloy is: Mg and Mg-30wt.%Ca master alloy are weighed according to the mass ratio of each element, and 5% of magnesium is additionally added to balance the burn-off during the smelting process, and then the raw materials are placed in a graphite crucible, and RJ-6 flux is added to cover the metal, and then heated to 750-760°C in a resistance furnace, and then cooled to 720-730°C and kept warm for 15-20 minutes, fully stirred during the insulation period, and then the molten metal is poured into a stainless steel mold to solidify.
[0016] Preferably, in step 2, the Mg-Ca binary alloy is first extruded and deformed on a metal extruder, and then crushed and pulverized by a high-energy ball mill under argon protection, the ball milling time is 1 hour, the ball-to-material ratio is 40:1, and the rotation speed is 1300 rpm.
[0017] Preferably, in step three, the composite metal carbide and Ni powder are first mixed with Mg-Mg2Ca alloy particles in a ball mill for 5 to 10 minutes, and then high-energy ball milling is performed under argon protection for 1 hour, with a ball-to-material ratio of 20:1 and a rotation speed of 1300 rpm.
[0018] Preferably, in step 4, a fully automatic high-speed double-pressure rotary tablet press is used for tableting, the pressure used is 10-15 MPa, the tableting is performed in one step without holding pressure, and the diameter of the material obtained by pressing is 12-20 mm and the thickness is 1-10 mm.
[0019] A magnesium-based composite material with a high hydrolysis hydrogen production conversion rate comprises Mg-Mg2Ca-composite metal carbide-Ni composite powder, wherein the composite metal carbide is TiC and ZrC in a mass ratio of 1:1; the mass fraction of the composite metal carbide is 3% to 5%, the mass fraction of Ni is 4% to 8%, and the remainder is Mg-Mg2Ca alloy particles.
[0020] A magnesium-based composite material with a high hydrolysis hydrogen production conversion rate, with a hydrogen production conversion rate of more than 99.0% within 120 minutes.
[0021] A magnesium-based composite material with a high hydrolysis hydrogen production conversion rate is used in mobile hydrogen production, which includes portable power sources, drones, unmanned underwater vehicles, and robots.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) In the Mg-Mg2Ca-composite metal carbide-Ni hydrolysis hydrogen production composite material prepared by the present invention, both Mg and Mg2Ca phases can spontaneously react with water to generate hydrogen, and the byproducts Mg(OH)2 and Ca(OH)2 are non-polluting to the environment. In addition, Mg and Mg2Ca phases are distributed alternately in layers, which helps to peel off the passivation layers of Mg(OH)2 and Ca(OH)2 during the hydrolysis process. The superhard composite metal carbide can effectively refine the alloy particles and evenly distribute the transition metal Ni on the surface and subsurface of the particles, so that a large number of primary cells are formed between Ni and Mg / Mg2Ca phases. At the same time, the composite metal carbides can act synergistically to effectively accelerate the electron transfer between Ni and Mg / Mg2Ca phases during the hydrolysis process. Through the bridge effect of the composite metal carbide, the electrons and hydrogen atoms in the hydrolysis process are quickly transferred, thereby significantly accelerating the rate of hydrogen production by hydrolysis. The superhard composite metal carbide can also effectively divide the matrix particles, thereby improving the overall hydrogen production conversion rate.
[0024] (2) The Mg-Mg2Ca-composite metal carbide-Ni hydrolysis hydrogen production composite material obtained by the present invention has a fast hydrogen production rate and a high raw material utilization rate.
[0025] (3) The preparation process of the present invention is simple, inexpensive, and suitable for large-scale production.
[0026] In summary, the preparation process of the present invention is simple, low in cost, and short in time. The composite material can quickly prepare a large amount of hydrogen with a high conversion rate and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 XRD and microstructure SEM / BSE images of the Mg-Ca binary alloy of Example 1 of the present invention;
[0028] Figure 2 is a SEM image of the Mg-Mg2Ca-composite metal carbide-Ni composite powder in Example 1 of the present invention;
[0029] Figure 3 This is a microstructure photograph of the tablet obtained in Example 1 of the present invention;
[0030] Figure 4 The phenomenon of hydrogen production by reaction of the tablet obtained in Example 1 of the present invention with seawater at normal temperature and pressure and the kinetic curve of hydrogen production by hydrolysis;
[0031] Figure 5 XRD and microstructure SEM / BSE images of the Mg-Ca binary alloy of Example 2 of the present invention;
[0032] Figure 6 This is a microstructure photograph of the tablet obtained in Example 2 of the present invention;
[0033] Figure 7 The hydrolysis hydrogen production kinetic curve of the compressed tablet obtained in Example 2 of the present invention reacting with seawater to produce hydrogen at room temperature and pressure;
[0034] Figure 8 XRD and microstructure SEM / BSE images of the Mg-Ca binary alloy of Example 3 of the present invention;
[0035] Fig. 9 This is a microstructure photograph of the tablet obtained in Example 3 of the present invention;
[0036] Fig.10 The hydrolysis hydrogen production kinetic curve of the compressed tablet obtained in Example 3 of the present invention reacting with seawater to produce hydrogen at room temperature and pressure;
[0037] Fig.11 XRD and microstructure SEM / BSE images of the Mg-Ca binary alloy of Comparative Example 1;
[0038] Fig.12 The hydrolysis hydrogen production kinetic curve of the tablet obtained in Comparative Example 1 reacting with seawater at room temperature and pressure to produce hydrogen;
[0039] Fig.13 This is the hydrolysis hydrogen production kinetic curve of the compressed tablet obtained in Comparative Example 2 reacting with seawater at normal temperature and pressure to produce hydrogen. DETAILED DESCRIPTION
[0040] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0041] Example 1
[0042] A method for preparing a magnesium-based composite material with a high hydrolysis hydrogen production conversion rate comprises the following steps: mixing metal Mg (99.99%) and Mg-30wt.%Ca master alloy in proportion, wherein the mass fraction of Ca is 13%, the mass fraction of Mg is 87%, and 5% of magnesium is additionally added to balance the burning loss and oxidation during the smelting process; then placing the above metal raw material blocks in a graphite crucible, adding RJ-6 flux to cover the metal, and then heating to 750°C in a resistance furnace, and then cooling to 720°C and keeping the temperature for 15 minutes, stirring fully during the keeping temperature to make it a macroscopically uniform melt, and then pouring the metal melt into a stainless steel mold for solidification, and then removing the surface covering agent and oxide layer, the alloy consists of primary Mg and eutectic structure, the eutectic structure consists of Mg and Mg2Ca two phases, the two phases are alternately distributed and are in a lamellar shape, and its XRD and microstructure (SEM / BSE) are as follows: Figure 1 As shown. 87 Ca 13The alloy was first extruded and deformed on a metal extruder, and then crushed and powdered using a high-energy ball mill under argon protection. The ball milling time was 1 hour, the ball-to-material ratio was 40:1, and the rotation speed was 1300 rpm.
[0043] 3wt.% TiC, ZrC and 5wt.% Ni in a mass ratio of 1:1 were mixed with the above Mg-Mg2Ca alloy particles in a ball mill for 5 minutes, and then high-energy ball milling was performed under argon protection for 1 hour, with a ball-to-material ratio of 20:1 and a rotation speed of 1300 rpm. The SEM image of the sample after ball milling is as follows Figure 2 As shown in the figure, it can be seen that the composite metal carbide can effectively refine the alloy particles and evenly distribute the transition metal Ni on the surface and subsurface of the Mg-Mg2Ca alloy particles.
[0044] The tablets are pressed using a fully automatic high-speed double-pressure rotary tablet press with a pressure of 15MPa. The tablets are pressed in one go without the need for pressure maintenance. The diameter of the pressed material is 13mm and the thickness is 1mm. Figure 3 This is a microstructure photo of the composite material tablet (secondary electron morphology). Figure 3 The right picture is an enlarged picture of the left picture. It can be seen from the picture that the ball-milled particles of irregular shapes and sizes are closely arranged, and there are a lot of gaps between the particles, which is conducive to the transfer of aqueous solution in the process of hydrolysis hydrogen production. Figure 4 The phenomenon of hydrogen production by reaction of composite material tablets with seawater at room temperature and pressure and the kinetic curve of hydrogen production by hydrolysis are shown. The prepared composite material can produce up to 859.2 mL / g of hydrogen within 120 minutes, with a conversion rate of up to 99.6%.
[0045] A magnesium-based composite material with a high hydrolysis hydrogen production conversion rate, comprising Mg-Mg2Ca-composite metal carbide-Ni composite powder, wherein the composite metal carbide is TiC and ZrC in a mass ratio of 1:1; the mass fraction of the composite metal carbide is 3%, the mass fraction of Ni is 5%, and the remainder is Mg-Mg2Ca alloy particles.
[0046] A magnesium-based composite material with a high hydrolysis hydrogen production conversion rate is used in mobile hydrogen production, which includes portable power sources, drones, unmanned underwater vehicles, and robots.
[0047] Example 2
[0048] A preparation method of a magnesium-based composite material with a high hydrolysis hydrogen production conversion rate comprises the following steps: metal Mg (99.99%) and Mg-30wt.%Ca master alloy are proportioned, wherein the mass fraction of Ca is 16%, the mass fraction of Mg is 84%, and 5% of magnesium is additionally added to balance the burning loss and oxidation during the smelting process; then the above metal raw material blocks are placed in a graphite crucible, RJ-6 flux is added to cover the metal, and then heated to 760°C in a resistance furnace, and then cooled to 730°C and kept warm for 20 minutes, and fully stirred during the heat preservation period to make it a macroscopically uniform melt, and then the metal melt is poured into a stainless steel mold for solidification, and then the surface covering agent and oxide layer are removed, the alloy is composed of primary Mg and eutectic structure, the eutectic structure is composed of Mg and Mg2Ca two phases, the two phases are alternately distributed and are in a lamellar shape, and its XRD and microstructure (SEM / BSE) are as follows: Figure 5 As shown. 84 Ca 16 The alloy was first extruded and deformed on a metal extruder, and then crushed and powdered using a high-energy ball mill under argon protection. The ball milling time was 1 hour, the ball-to-material ratio was 40:1, and the rotation speed was 1300 rpm.
[0049] 5wt.% TiC, ZrC and 4wt.% Ni in a mass ratio of 1:1 were mixed with the above-mentioned Mg-Mg2Ca alloy particles in a ball mill for 10 minutes, and then high-energy ball milling was carried out under argon protection for 1 hour, with a ball-to-material ratio of 20:1 and a rotation speed of 1300 rpm.
[0050] The tablets were pressed using a fully automatic high-speed double-pressure rotary tablet press with a pressure of 10 MPa. The tablets were pressed in one go without the need for pressure maintenance. The material obtained by pressing had a diameter of 12 mm and a thickness of 1.3 mm.
[0051] The Mg-Ca binary alloy obtained in this embodiment is composed of primary Mg and eutectic structure. The eutectic structure is composed of two phases, Mg and Mg2Ca, which are alternately distributed in a lamellar shape. Its XRD and microstructure (SEM / BSE) are as follows: Figure 5 As shown, Figure 6 This is a microstructure photo of the composite material tablet (secondary electron morphology). Figure 6 The right picture is an enlarged picture of the left picture. It can be seen from the picture that the ball-milled particles of irregular shapes and sizes are closely arranged, and there are a lot of gaps between the particles, which is conducive to the transfer of aqueous solution in the process of hydrolysis hydrogen production. Figure 7 This is the kinetic curve for hydrogen production by hydrolysis of composite material tablets in seawater. The prepared composite material can produce up to 843.1 mL / g of hydrogen within 120 min, with a conversion rate of up to 99.1%.
[0052] A magnesium-based composite material with a high hydrolysis hydrogen production conversion rate, comprising Mg-Mg2Ca-composite metal carbide-Ni composite powder, wherein the composite metal carbide is TiC and ZrC in a mass ratio of 1:1; the mass fraction of the composite metal carbide is 5%, the mass fraction of Ni is 4%, and the remainder is Mg-Mg2Ca alloy particles.
[0053] A magnesium-based composite material with a high hydrolysis hydrogen production conversion rate is used in mobile hydrogen production, which includes portable power sources, drones, unmanned underwater vehicles, and robots.
[0054] Example 3
[0055] A method for preparing a magnesium-based composite material with a high hydrolysis hydrogen conversion rate comprises the following steps: mixing metal Mg (99.99%) and Mg-30wt.%Ca master alloy in proportion, wherein the mass fraction of Ca is 8%, the mass fraction of Mg is 92%, and 5% of magnesium is additionally added to balance the burning loss and oxidation during the smelting process; then placing the above metal raw material blocks in a graphite crucible, adding RJ-6 flux to cover the metal, and then heating to 750°C in a resistance furnace, and then cooling to 720°C and keeping the temperature for 15 minutes, stirring fully during the keeping temperature to make it a macroscopically uniform melt, and then pouring the metal melt into a stainless steel mold for solidification, and then removing the surface covering agent and oxide layer, the alloy consists of primary Mg and eutectic structure, the eutectic structure consists of Mg and Mg2Ca two phases, the two phases are alternately distributed and are in a lamellar shape, and its XRD and microstructure (SEM / BSE) are as follows: Figure 8 As shown. 92 The Ca8 alloy was first extruded and deformed on a metal extruder, and then crushed and pulverized using a high-energy ball mill under argon protection. The ball milling time was 1 hour, the ball-to-material ratio was 40:1, and the rotation speed was 1300 rpm.
[0056] 5wt.% TiC, ZrC and 8wt.% Ni in a mass ratio of 1:1 were mixed with the above-mentioned Mg-Mg2Ca alloy particles in a ball mill for 5 minutes, and then high-energy ball milling was carried out under argon protection for 1 hour, with a ball-to-material ratio of 20:1 and a rotation speed of 1300 rpm.
[0057] The tablets were pressed using a fully automatic high-speed double-pressure rotary tablet press with a pressure of 15 MPa. The tablets were pressed in one go without the need for pressure maintenance. The material obtained by pressing had a diameter of 15 mm and a thickness of 2.1 mm.
[0058] The Mg-Ca binary alloy obtained in this embodiment is composed of primary Mg and eutectic structure. The eutectic structure is composed of two phases, Mg and Mg2Ca, which are alternately distributed in a lamellar shape. Its XRD and microstructure (SEM / BSE) are as follows: Figure 8 As shown, Fig. 9 This is a microstructure photo of the composite material tablet (secondary electron morphology). Fig. 9 The right picture is an enlarged picture of the left picture. It can be seen from the picture that the ball-milled particles of irregular shapes and sizes are closely arranged, and there are a lot of gaps between the particles, which is conducive to the transfer of aqueous solution in the process of hydrolysis hydrogen production. Fig.10 The kinetic curve of hydrogen production by hydrolysis of composite material tablets in seawater shows that the prepared composite material can produce up to 828.8 mL / g of hydrogen within 120 min, with a conversion rate of up to 99.5%.
[0059] A magnesium-based composite material with a high hydrolysis hydrogen production conversion rate comprises Mg-Mg2Ca-composite metal carbide-Ni composite powder, wherein the composite metal carbide is TiC and ZrC in a mass ratio of 1:1; the mass fraction of the composite metal carbide is 5%, the mass fraction of Ni is 8%, and the remainder is Mg-Mg2Ca alloy particles.
[0060] A magnesium-based composite material with a high hydrolysis hydrogen production conversion rate is used in mobile hydrogen production, which includes portable power sources, drones, unmanned underwater vehicles, and robots.
[0061] Example 4
[0062] The only difference between this embodiment and embodiment 1 is that the material obtained by pressing has a diameter of 20 mm and a thickness of 10 mm.
[0063] Comparative Example 1
[0064] A preparation method of a magnesium-based composite material comprises the following steps: mixing metal Mg (99.99%) and Mg-30wt.%Ca master alloy in proportion, wherein the mass fraction of Ca is 3%, the mass fraction of Mg is 97%, and 5% of magnesium is additionally added to balance the burning loss and oxidation during the smelting process; then placing the above metal raw material blocks in a graphite crucible, adding RJ-6 flux to cover the metal, and then heating to 750°C in a resistance furnace, and then cooling to 720°C and keeping the temperature for 15 minutes, stirring fully during the keeping temperature to make it a macroscopically uniform melt, and then pouring the metal melt into a stainless steel mold for solidification, and then removing the surface covering agent and oxide layer, the alloy is composed of primary Mg and a small amount of eutectic structure, the eutectic structure is composed of Mg and Mg2Ca two phases, the two phases are alternately distributed and are in a lamellar shape, and its XRD and microstructure (SEM / BSE) are as follows: Fig.11 As shown. 97 The Ca3 alloy was first extruded and deformed on a metal extruder, and then crushed and pulverized using a high-energy ball mill under argon protection. The ball milling time was 1 hour, the ball-to-material ratio was 40:1, and the rotation speed was 1300 rpm.
[0065] 5wt.% TiC, ZrC and 8wt.% Ni in a mass ratio of 1:1 were mixed with the above-mentioned Mg-Mg2Ca alloy particles in a ball mill for 5 minutes, and then high-energy ball milling was carried out under argon protection for 1 hour, with a ball-to-material ratio of 20:1 and a rotation speed of 1300 rpm.
[0066] The tablets are pressed using a fully automatic high-speed double-pressure rotary tablet press with a pressure of 15MPa. The tablets are pressed in one go without the need for pressure maintenance. The diameter of the pressed material is 13mm and the thickness is 1mm. Fig.12 This is the kinetic curve of hydrogen production by hydrolysis of the composite material tablet in seawater. The amount of hydrogen produced by the prepared composite material within 120 minutes is only 663.2 mL / g, and the conversion rate is 78.1%.
[0067] Comparative Example 2
[0068] A preparation method of a magnesium-based composite material comprises the following steps: mixing metal Mg (99.99%) and Mg-30wt.%Ca master alloy in proportion, wherein the mass fraction of Ca is 8%, the mass fraction of Mg is 92%, and 5% of magnesium is additionally added to balance the burning loss and oxidation during the smelting process; then placing the above metal raw material blocks in a graphite crucible, adding RJ-6 flux to cover the metal, and then heating to 750°C in a resistance furnace, and then cooling to 720°C and keeping the temperature for 15 minutes, stirring fully during the keeping temperature to make it a macroscopically uniform melt, and then pouring the metal melt into a stainless steel mold for solidification, and then removing the surface covering agent and oxide layer, the alloy consists of primary Mg and eutectic structure, the eutectic structure consists of Mg and Mg2Ca two phases, the two phases are alternately distributed and are in a lamellar shape, and its XRD and microstructure (SEM / BSE) are as follows: Figure 8 As shown. 92 The Ca8 alloy was first extruded and deformed on a metal extruder, and then crushed and pulverized using a high-energy ball mill under argon protection. The ball milling time was 1 hour, the ball-to-material ratio was 40:1, and the rotation speed was 1300 rpm.
[0069] 5wt.% SiC and 8wt.% Ni were mixed with the above Mg-Mg2Ca alloy particles in a ball mill for 5 minutes, and then high-energy ball milling was performed under argon protection for 1 hour, with a ball-to-material ratio of 20:1 and a rotation speed of 1300 rpm.
[0070] The tablets are pressed using a fully automatic high-speed double-pressure rotary tablet press with a pressure of 15MPa. The tablets are pressed in one go without the need for pressure maintenance. The diameter of the pressed material is 15mm and the thickness is 2.1mm. Fig.13The kinetic curve of hydrogen production by hydrolysis of the composite material tablet in seawater shows that the amount of hydrogen produced by the prepared composite material within 120 min is only 668.6 mL / g, and the conversion rate is 80.2%, which is significantly lower than that of the sample to which TiC and ZrC are added under the same conditions (Example 3), indicating that TiC and ZrC promote electron transfer and hydrogen atom diffusion during the hydrolysis of magnesium-based materials, and play an important role in promoting the overall hydrolysis hydrogen production conversion rate of the material.
[0071] Comparative Example 3
[0072] The difference between this comparative example and comparative example 2 is that 5wt.% of SiC is replaced by 5wt.% of TiC. The composite material prepared in this comparative example produces 732.6mL / g of hydrogen within 120min, and the conversion rate is 88.1%, which is significantly lower than the sample to which TiC and ZrC are added under the same conditions (Example 3), indicating that TiC and ZrC act synergistically and work together to promote the electron transfer and hydrogen atom diffusion in the hydrolysis process of magnesium-based materials, and play an important role in promoting the overall hydrolysis hydrogen production conversion rate of the material.
[0073] Comparative Example 4
[0074] The only difference between this comparative example and comparative example 2 is that 5 wt. % of SiC is replaced by 5 wt. % of ZrC.
[0075] The amount of hydrogen produced by the composite material prepared in this comparative example within 120 minutes is only 716.8 mL / g, and the conversion rate is 86.0%, which is significantly lower than the sample to which TiC and ZrC are added under the same conditions (Example 3), indicating that TiC and ZrC act synergistically and work together to promote electron transfer and hydrogen atom diffusion during the hydrolysis of magnesium-based materials, and play an important role in promoting the overall hydrolysis hydrogen production conversion rate of the material.
[0076] It should be understood that in order to streamline the present disclosure and aid in understanding one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting the intention that the claimed invention requires more features than those expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Therefore, the claims that follow the detailed description are hereby expressly incorporated into the detailed description, with each claim itself serving as a separate embodiment of the present invention.
[0077] Although the present invention has been described according to a limited number of embodiments, it will be apparent to those skilled in the art, with the benefit of the above description, that other embodiments may be envisioned within the scope of the invention thus described. In addition, it should be noted that the language used in this specification is selected primarily for readability and teaching purposes, rather than for explaining or defining the subject matter of the present invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is illustrative, not restrictive, with respect to the scope of the present invention, which is defined by the appended claims.
[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a magnesium-based composite material with a high hydrolysis hydrogen production conversion rate, characterized in that: The following steps are involved: Step 1, preparing Mg-Ca binary alloy; Step 2, mechanically crushing the obtained Mg-Ca binary alloy to obtain Mg-Mg2Ca alloy particles; Step 3, adding composite metal carbide and Ni powder to the Mg-Mg2Ca alloy particles and then performing high-energy ball milling to obtain Mg-Mg2Ca-composite metal carbide-Ni composite powder; Step 4, placing the Mg-Mg2Ca-composite metal carbide-Ni composite powder into a tablet pressing mold, and using a tablet press to press it into a block or sheet material to obtain a magnesium-based composite material with a high hydrolysis hydrogen production conversion rate; In the Mg-Mg2Ca-composite metal carbide-Ni composite powder, the composite metal carbide is TiC and ZrC with a mass ratio of 1:1; the mass fraction of the composite metal carbide is 3%~5%, and the mass fraction of Ni is 4%~8%.
2. The preparation method according to claim 1, characterized in that: In the Mg-Ca binary alloy, the mass fraction of the Ca element ranges from 8% to 16%, and the balance is Mg.
3. The preparation method according to claim 1, characterized in that: In step 1, the preparation method of the Mg-Ca binary alloy is as follows: Mg and Mg-30wt.%Ca master alloy are weighed according to the mass ratio of each element, and 5% of magnesium is additionally added to balance the burn-off during the smelting process, and then the raw materials are placed in a graphite crucible, and RJ-6 flux is added to cover the metal, and then heated to 750-760°C in a resistance furnace, and then cooled to 720-730°C and kept warm for 15-20 minutes, and fully stirred during the insulation period, and then the molten metal is poured into a stainless steel mold to solidify.
4. The preparation method according to claim 1, characterized in that: In step 2, the Mg-Ca binary alloy is first extruded and deformed on a metal extruder, and then crushed and powdered by a high-energy ball mill under argon protection. The ball milling time is 1 hour, the ball-to-material ratio is 40:1, and the rotation speed is 1300 rpm.
5. The preparation method according to claim 1, characterized in that: In step three, the composite metal carbide and Ni powder are first mixed with the Mg-Mg2Ca alloy particles in a ball mill for 5 to 10 minutes, and then high-energy ball milling is performed under argon protection for 1 hour, with a ball-to-material ratio of 20:1 and a rotation speed of 1300 rpm.
6. The preparation method according to claim 1, characterized in that: In step 4, a fully automatic high-speed double-pressure rotary tablet press is used for tableting. The pressure used is 10-15 MPa. The tablets are pressed in one go without holding the pressure. The diameter of the pressed material is 12-20 mm and the thickness is 1-10 mm.
7. A magnesium-based composite material with high hydrolysis hydrogen conversion rate, characterized in that: The composition is Mg-Mg2Ca-composite metal carbide-Ni composite powder, wherein the composite metal carbide is TiC and ZrC with a mass ratio of 1:1; the mass fraction of the composite metal carbide is 3%~5%, the mass fraction of Ni is 4%~8%, and the balance is Mg-Mg2Ca alloy particles.
8. The magnesium-based composite material with high hydrolysis hydrogen production conversion rate according to claim 7, characterized in that: The conversion rate of hydrogen production is as high as over 99.0% within 120 minutes.
9. The use of a magnesium-based composite material with high hydrolysis hydrogen production conversion rate according to claim 7 or 8 in mobile hydrogen production, characterized in that: Mobile hydrogen production includes portable power sources, drones, unmanned underwater vehicles, and robots.
Citation Information
Cited By
Composite material for improving magnesium-based hydrolysis hydrogen production performance, preparation method and application
CN122081734A